(untitled) (Academic journal Industrial Machine Building Civil Engineering, 2023)
Reducing the use of cement and reducing the weight of concrete in bending reinforced concrete elements is an important task in modern construction. To solve this problem, various methods are being implemented, including the use of both removable and non-removable void formers, and the combination of several materials (e.g., heavy in the compressed zone and light in the tensile zone of concrete) for their mutually beneficial joint operation. The paper provides an overview of several experimental and theoretical studies in these areas, which substantiate the possibility and feasibility of reducing the strength of concrete in the tensile zone of bending reinforced concrete structures, and as a result, reducing the consumption of cement for the preparation of concrete mix for structures, without prestressing the latter. The use of two- and multi-layer elements reduces the dead weight of structures, improves sound and thermal insulation properties, which leads to savings in materials, labor and financial resources. The right choice of material for each layer allows for the creation of structures with high performance characteristics.